THE APPLICATION OF THE SINGING METHOD ASSISTED BY AUDIO VISUAL MEDIA IN IMPROVING STUDENT LEARNING OUTCOMES IN THE HUMAN RESPIRATORY SYSTEM MATERIAL OF SD NEGERI 32 BANDA ACEH - Azizah, Roja Nur; Safiah, Intan; Tursinawati, Tursinawati (Elementary Education Research, 2025)
In science learning, there are many complaints from teachers because student learning outcomes are still below the average value determined by the school, especially in the subject of human respiratory organs. This can be proven by looking at the results of students' daily tests. This research aims to determine student activities and teacher activities during learning and to determine the increase in student learning outcomes after implementing the singing method. The results of data analysis show that the application of the singing method assisted by audio-visual media on respiratory organ material in class V humans at SD Negeri 32 Banda Aceh has increased: (1) student activity during learning in cycle I with a fairly good criteria score (3.3) in the cycle II has a good criteria value (3.6) and cycle III has a very good criteria value (4.5); (2) teacher activities during learning cycle I with a fairly good criteria score (3.4), in cycle II it has a good criteria score (3.7) and cycle III has a very good criteria score (4.7): and (3) completeness student learning after following the learning process by applying the singing method, students obtained in cycle I (53.33%) in cycle II became (66.67%) and cycle III became (86.67%). The conclusion in this research is that learning by applying the singing method can improve student learning outcomes. This can be seen from student activities, teacher activities, and the completeness of learning outcomes that have reached the KKM after participating in the lesson.